Essays on monetary policy and banking - Viegi, Nicola (University of Pretoria, 2018)
The size of the nancial sector in South Africa has grown signi cantly over the past fi fteen years to now almost three times the size of the economy. Parallel to that growth is the growth of the banking sector, speci cally the six commercial banks that dominate the sector. This expansion has both monetary policy and financial stability implications. The objectives of this PhD are to: (1) study the importance of internal and external variables for nancial stability; (2) determine the role of the structure of the banking sector in the transmission of monetary policy and macroeconomic shocks; and (3) understand financial stability in the context of both the South African financial system structure and demographic dynamics. We start with a cross-sectional analysis of how external and internal variables affect local fi nancial stability. We fi nd that local variables such as credit, stock market capitalisation and real exchange rate growth are better candidates for understanding local fi nancial stability for both the high and the upper middle income countries. Next we explore monetary policy and financial stability in the context of the South African banking system structure and socio-economic dynamics. An empirical analysis of the bank lending channel indicate that the effect of monetary policy is asymmetric - small banks are more affected by a contractionary monetary policy, whereas the big banks can adjust their loan portfolios to cushion the effects. However, these results (as well as the current South African literature) assume that the transmission of monetary policy and the way the exogenous shocks are generated have remained constant over time. We show that following the 2008 fi nancial crisis, both the big banks and small banks became more responsive to a monetary policy shock. We then develop a dynamic stochastic general equilibrium model to analyse - financial stability for the South African banking sector. The main elements to capture the socio-demographic characteristics include banking and household heterogeneity. We incorporate the relative consumption motive to capture the culture of "keeping up with the Joneses" that has resulted in high consumption driven by debt. The heterogeneity of the banking sector is motivated by the structure of the banking sector, which has enabled the existence of the big and the small banks serving the high-income and low-income households respectively. We calibrate the model using South African data. Our model shows that liquidity injections in the presence of the relative consumption motive increase loan demand whilst adverse shocks to the banks' balance sheets have welfare effects, especially for low-income households.